Optimizing Feedback for Elementary Students through Structured SMART-Based Assessment Tools - Lestari, Kadek Intan Dwi; Sari, Ni Made Dainivitri Sinta (Journal of Education Technology, 2024)
The provision of optimal feedback to elementary school students often lacks effectiveness due to the absence of structured assessment instruments. This study aims to develop a SMART-based (Specific, Measurable, Achievable, Relevant, Time-bound) non-test assessment instrument that is valid, practical, and effective in supporting feedback optimization. The research employed a descriptive quantitative method with a Research and Development (R&D) approach. The trial subjects included fourth-grade homeroom teachers and fourth-grade elementary students. Instrument validity was assessed using Gregory's calculation theory, while practicality was evaluated based on field implementation. The instrument integrates SMART principles to ensure its measurability in providing feedback that is specific, relevant, and aligned with students' needs. The findings indicate that the instrument has linguistic, content, and design validity, categorized as "Highly Valid." It was also deemed practical by teachers in its application, proving effective for use in the learning process. In conclusion, the SMART-based non-test assessment instrument can assist teachers in delivering optimal feedback, supporting the achievement of learning objectives, and is suitable for sustainable implementation.